Cellular mechanisms underlying cholinergic and noradrenergic modulation of neuronal firing mode in the cat and guinea pig dorsal lateral geniculate nucleus - McCormick, DA (J Neurosci, 1992)
The functional properties, ionic basis, and possible convergence and interaction of postsynaptic actions mediated by muscarinic and alpha 1- adrenergic receptors were examined in cat and guinea pig dorsal lateral geniculate (LGNd) neurons maintained in thalamic slices in vitro. The possible involvement of GTP-binding proteins was also examined. Extracellular recordings from cat LGNd revealed the presence of two subpopulations of neurons. The most prevalent generated rhythmic high- frequency (300–500 Hz) bursts of two to six action potentials each, with an interburst frequency of 1–3 Hz. Intracellular recordings revealed that this activity is typical of thalamocortical relay cells in the apparent absence of neuromodulatory input. Application of ACh or noradrenaline (NA) to rhythmically oscillating neurons in the cat LGNd resulted in cessation of this activity followed by the appearance of single spike firing. Intracellular recordings revealed that this change in firing mode was associated with a depolarization of the neuron out of the range of intrinsic rhythmic oscillation and into or near the single spike firing mode. The voltage characteristics of the current underlying the cholinergic and noradrenergic slow depolarization were investigated in guinea pig LGNd neurons. Application of the muscarinic agonist acetyl-beta-methylcholine (MCh) to presumed relay neurons resulted in a hyperpolarization due to the activation of an outward K+ current. This response was followed by a slow depolarization due to reduction of a relatively non-voltage-dependent potassium current distinct from IM and IAHP. Application of NA resulted in a slow depolarization that was also associated with reduction of this relatively linear K+ current. The MCh- and NA-induced slow depolarizations displayed the property of occlusion, indicating convergence of action. However, these responses were mediated by pharmacologically distinct receptors since the MCh-induced reduction in K+ current was blocked by scopolamine while that induced by NA was blocked by the alpha 1-adrenoceptor antagonist prazosin. Intracellular diffusion of GTP-gamma-S resulted in the inward current responses to NA and MCh being irreversible, suggesting the possible involvement of a G- protein. Prior exposure to pertussis toxin did not affect the inward current response to NA and MCh, while the outward K+ current responses induced by application of MCh or the GABAB agonist baclofen were blocked. These results reveal that activation of muscarinic or alpha 1- adrenergic postsynaptic receptors in the LGNd result in a shift in firing mode from rhythmic oscillation to tonic single spike activity through a decrease in a relatively linear K+ current mediated through a pertussis toxin-insensitive G-protein.(ABSTRACT TRUNCATED AT 400 WORDS)